Hydromagnetic natural convection flows resulting from the combined buoyancy effects of thermal and mass diffusion - Ram P.C.; Singh S.S.; Agarwal H.L. (My University, 2025)
Natural convection of an electrically conducting fluid produced by the interaction of the force of gravity and density differences caused by the simultaneous diffusion of thermal energy and chemical species in the presence of a uniform transverse magnetic field is discussed. On thermal boundary layer thickness, concentration boundary layer thickness Xt and Xc have been calculated for different values of Prandtl number. A direct relation between the film thickness and distance travelled is presented and it is found that the film thickness approaches the uniform film thickness asymptotically. © 1977 with the authors.